Harmonizing antibiotic regimens with renal replacement therapy. Issue 9 (1st September 2020) - Jang, Soo Min; Lewis, Susan J.; Mueller, Bruce A.
ABSTRACT: Introduction : Critically ill patients with acute kidney injury often require renal replacement therapy and antibiotic therapy. Mortality rates are high in these patients, possibly due to ineffective dosing due to altered pharmacokinetic profiles and drug removal by renal replacement therapy. Areas covered : The main types of renal replacement therapies are intermittent hemodialysis, prolonged intermittent renal replacement therapy and continuous renal replacement therapy. Each of these renal replacement therapies may have drastic, yet different, effects on antibiotic serum concentration profiles. Moreover, three antibiotic administration strategies are often used: (1) standard infusion; (2) extended infusion; and (3) continuous infusion. A literature review was conducted on Medline in December 2019 to identify pertinent research. Expert opinion : Renal replacement therapies used in the treatment of acute kidney injury in critically ill patients usually complicates antibiotic use. Although antibiotic toxicity can be seen, most studies find that these patients do not receive sufficient antibiotic doses to achieve desired pharmacodynamic targets. Clinicians should dose antibiotics to match renal replacement therapy drug clearance characteristics to antibiotic pharmacodynamic profiles.